Bunk [compact disc, unabridged] : the rise of hoaxes, humbug, plagiarists, phonies, post-facts, and fake news - Young, Kevin, 1970- (HighBridge, a division of Recorded Books, 2017)
Kevin Young traces the history of the hoax as a peculiarly American phenomenon, examining what motivates hucksters and makes people so gullible. He chronicles how Barnum came to fame by displaying figures like Joice Heth, a black woman whom he pretended was the 161-year-old nursemaid to George Washington, and What Is It?, an African American man Barnum professed was a newly discovered missing link in evolution.